Sistematik Literatur Review dampak Kepercayaan Diri pada Kesuksesan Pengusaha - Gunawan, Indra; Rahmat Syah, Tantri Yanuar (IPM2KPE, 2024)
This study aims to examine the impact of self-confidence on entrepreneurial success through a systematic review of existing literature. Self-confidence is an important psychological factor in entrepreneurship, influencing risk-taking, innovation, persistence, and business performance. The research method used is a literature review involving the search and analysis of various relevant empirical studies. The results of the study indicate that high self-confidence is positively correlated with greater risk-taking ability, creativity in innovation, resilience in the face of failure, and achievement of better business performance. In addition, factors such as experience, education and entrepreneurial training, social support, and culture and economic climate are also found to play a significant role in shaping and strengthening entrepreneurial self-confidence. This study also identifies several challenges and gaps in previous research, such as variations in the definition and measurement of self-confidence, and the lack of qualitative and longitudinal approaches. Keywords: Self-confidence, Entrepreneurship, Entrepreneurial Success